Performance of the LHCb Outer Tracker - Arink, R.; Bachmann, Sebastian; Färber, Christian; Bien, Alexander; Blouw, Johan; Gersabeck, Evelina; Grillo, Lucia; Langenbruch, Christoph; Linn, Christian; Meißner, Marco; Seyfert, Paul; Uwer, Ulrich; et al. (Journal of Instrumentation, 2014)
The LHCb Outer Tracker is a gaseous detector covering an area of 5 × 6 m2 with 12 double layers of straw tubes. The detector with its services are described together with the commissioning and calibration procedures. Based on data of the first LHC running period from 2010 to 2012, the performance of the readout electronics and the single hit resolution and efficiency are presented. The efficiency to detect a hit in the central half of the straw is estimated to be 99.2%, and the position resolution is determined to be approximately 200 μm. The Outer Tracker received a dose in the hottest region corresponding to 0.12 C/cm, and no signs of gain deterioration or other ageing effects are observed.